Costs of missing the Millennium Development Goal on gender equity - Abu-Ghaida, Dina (2004)
Uses the insights of recent findings about the effects of gender gaps in education on economic growth, fertility, child mortality, and under nutrition to estimate the losses that countries are likely to suffer if they do not meet the MDG of equity in primary and secondary education by 2005.